2020
DOI: 10.3389/fnbeh.2020.00132
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Tactile Stimulations Affect Genetic Generalized Epilepsy and Comorbid Depression-Like Behaviors

Abstract: Recent studies suggest that development of absence epilepsy and comorbid depression might be prevented by increased maternal care of the offspring, in which tactile stimulation induced by licking/grooming and non-nutritive contact seem to be crucial. In this study, we aimed to evaluate the effect of neonatal tactile stimulations (NTS) on absence epilepsy and depression-like behaviors in adulthood. Wistar Albino Glaxo from Rijswijk (WAG/Rij) rat pups with a genetic predisposition to absence epilepsy were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 82 publications
0
20
0
1
Order By: Relevance
“…The onset of absence epilepsy was delayed, and depression symptoms were reduced in the WAG/Rij pups that received intensive early maternal care by their foster Wistar mothers [15]. Our previous study showed that early neonatal tactile stimulations may decrease seizure activity and comorbid depression-like behaviors at adult ages in WAG/Rij rats [16]. These examples demonstrate the effect of early environmental factors on genetic absence epilepsy and comorbid depression.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The onset of absence epilepsy was delayed, and depression symptoms were reduced in the WAG/Rij pups that received intensive early maternal care by their foster Wistar mothers [15]. Our previous study showed that early neonatal tactile stimulations may decrease seizure activity and comorbid depression-like behaviors at adult ages in WAG/Rij rats [16]. These examples demonstrate the effect of early environmental factors on genetic absence epilepsy and comorbid depression.…”
Section: Introductionmentioning
confidence: 83%
“…Breaking more than 1 consecutive photobeam in the bottom set of photobeams was used as a measure of ambulatory activity. Total distance travelled (in cm) and numbers of stereotypic, ambulatory and vertical movements were analyzed [16].…”
Section: Locomotor Activity Testmentioning
confidence: 99%
“…Intensität von frühem Körperkontakt, Bindung und dem Risiko späterer psychischer Störungen wie z. B. Depression hingewiesen 35 40 41 42 43 44 45 . Früher Körperkontakt stellt folglich eine primärpräventive Intervention dar, die sich positiv auf die physische und psychosoziale Gesundheit auswirkt 46 .…”
Section: Meilensteine Der Berührungsforschungunclassified
“…Increased early maternal care not only exerts antiepileptogenic effects but also counteracts the development of comorbid depression in adult WAG/Rij rats [10]. A previous study by our group have shown that tactile stimulation (TS) during postnatal period in WAG/Rij rats genetically predisposed to epilepsy reduced epileptic activity and comorbid depression in adulthood [11].…”
Section: Introductionmentioning
confidence: 99%